Legal Protection of Workers' Rights by the Job Creation Law - Edi , Haryono; Kumar, Saurav (The International Journal of Law Review and State Administration, 2024)
This research aims to determine the legal protection of workers' rights, based on the Job Creation Law and the legal protection of the rights of workers of retirement age who remain employed. Can contribute thoughts both theoretically and practically to law in Indonesia. The research method used is normative juridical with primary, secondary, and tertiary law. Conclusion Constitutionally legal protection for workers is contained in Article 27 paragraph (2), Article 28D paragraph (1) and paragraph (2), Article 28H paragraph (3), and Article 28I (2) of the 1945 Constitution of the Republic of Indonesia. Legal protection of workers also in the International Covenant on Civil and Political Rights, as well as on Economic, Social and Cultural Rights, while from the perspective of the Job Creation Law, legal protection for workers is reflected in strategic policies in the employment sector, which protect and promote the welfare of workers. Second, the absence of strict regulations regarding the retirement age limit in the Job Creation Law has an impact on the rights of workers who are still employed at retirement age. There is no legal protection for those who are still employed at retirement age. What is stated in the Employment Agreement does not fulfill the principle of freedom of contract and the principle of complete balance between Workers and Employers according to the agreement.